(untitled) (Kinesiology, 2021)
This study investigated the death anxiety (DA) scores of participants in outdoor-adventure recreational (OAR) activities, and the relationship of the DA scores to several demographic features and experience of DA. The study included 589 individuals with various leisure-time OAR experience levels (131 women, 458 men; Mage=29.79±9.64). Their sports included climbing (n=200), scuba diving (n=142), and paragliding (n=247). DA was measured by the Thorson-Powell Death Anxiety Scale. Overall, the DA scores were low, with no significant differences between OAR activities. However, the DA scores were affected by age and gender, and length of OAR experience. More specifically, the DA scores were highest for 18-28-year-old participants, women, and participants with 4-6 years of middle-level OAR experience. Previous negative DA experiences did not increase the DA scores. Key words: adventure recreation, death, death anxiety, experience, outdoor sports